2002
DOI: 10.1002/cncr.10792
|View full text |Cite
|
Sign up to set email alerts
|

Survey of oncologists' perceptions of barriers to accrual of older patients with breast carcinoma to clinical trials

Abstract: BACKGROUNDPrior research has documented the under‐representation in clinical trials of older patients with cancer. In part of a larger study to test the magnitude of these barriers to entering eligible older patients with carcinoma of the breast into clinical trials (Cancer and Leukemia Group B [CALGB] trial 9670), barriers to accruing eligible older patients to clinical trials were obtained from the physician's perspective.METHODSOne hundred fifty‐six physicians (85% oncologists) who treated patients with bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
128
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 82 publications
1
128
0
1
Order By: Relevance
“…3), whereas 3 studies found provider attitudes to be a promoter of patient accrual. 18,20,26 The studies also reported that provider attitudes toward patient age, 11,12,16,17 comorbidities, 12,16,17 and disease stage, 16 physician perception of patient mistrust of researchers, 14,25 and lack of physician awareness about trials 14,23,25 were factors that prevented providers from enrolling their patients into clinical trials.…”
Section: Provider Barriers and Promotersmentioning
confidence: 99%
See 3 more Smart Citations
“…3), whereas 3 studies found provider attitudes to be a promoter of patient accrual. 18,20,26 The studies also reported that provider attitudes toward patient age, 11,12,16,17 comorbidities, 12,16,17 and disease stage, 16 physician perception of patient mistrust of researchers, 14,25 and lack of physician awareness about trials 14,23,25 were factors that prevented providers from enrolling their patients into clinical trials.…”
Section: Provider Barriers and Promotersmentioning
confidence: 99%
“…Of the 18 studies eligible for review, 3 were published before 1993, 10-12 2 were published between 1993 and 1999, 13,14 and 13 were published in 2000 or later (Table 1). [15][16][17][18][19][20][21][22][23][24][25][26][27] The study designs included a randomized controlled trial (n ¼ 1), concurrent controlled trial (n ¼ 1), casecontrol (n ¼ 1), and descriptive (n ¼ 15), with 4 of the studies also using qualitative techniques to facilitate in-depth assessments of physician attitudes and perceptions. Fourteen studies reported recruitment into treatment trials only [10][11][12][13][15][16][17][18][19][20][21][22]24,26 ; 3 studies reported recruitment into both prevention and treatment trials 14,25,27 ; and 1 study reported recruitment to a prevention trial (Table 1).…”
Section: Yield Of Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…50 Some evidence suggests that attitudinal barriers on the part of physicians play a role. 13,54,55,56 In addition, older patients are likely to have higher comorbid burdens, inducing clinical exclusions. 57,58 To the extent that trials seek to reflect the population of patients for whom new trial-proven treatments will be administered, better representation of older patients on trials is critical.…”
Section: Understanding Barriers To Clinical Trial Participationmentioning
confidence: 99%